2015
DOI: 10.1093/mnras/stv1791
|View full text |Cite
|
Sign up to set email alerts
|

Apparent age spreads in clusters and the role of stellar rotation

Abstract: We use the Geneva Syclist isochrone models that include the effects of stellar rotation to investigate the role that rotation has on the resulting colour-magnitude diagram (CMD) of young and intermediate age clusters. We find that if a distribution of rotation velocities exists within the clusters, rotating stars will remain on the main sequence (MS) for longer, appearing to be younger than non-rotating stars within the same cluster. This results in an extended main sequence turn-off (eMSTO) that appears at yo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
110
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(134 citation statements)
references
References 49 publications
23
110
1
Order By: Relevance
“…Brandt & Huang (2015a) used the rotating isochrones from the Geneva models (Ekström et al 2012;Georgy et al 2014) and showed that indeed stellar rotation can reproduce the eMSTOs observed in intermediate-age clusters. Niederhofer et al (2015a) used the same models and found that they predicted a relation between an apparent age spread and cluster age that matches the observations well. D 'Antona et al (2015) modelled the colour magnitude diagram (CMD) of NGC 1856 (∼300 Myr, ∼10…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Brandt & Huang (2015a) used the rotating isochrones from the Geneva models (Ekström et al 2012;Georgy et al 2014) and showed that indeed stellar rotation can reproduce the eMSTOs observed in intermediate-age clusters. Niederhofer et al (2015a) used the same models and found that they predicted a relation between an apparent age spread and cluster age that matches the observations well. D 'Antona et al (2015) modelled the colour magnitude diagram (CMD) of NGC 1856 (∼300 Myr, ∼10…”
Section: Introductionmentioning
confidence: 79%
“…Milone et al 2015;Correnti et al 2015;Milone et al 2016); Bastian et al 2016. It is now clear that the extended main sequence turn-off (eMSTO) phenomenon is a common feature of massive young (Bastian & Silva-Villa 2013;Niederhofer et al 2015a;Milone et al 2016); Bastian et al 2016 andintermediate-age clusters (e.g. Milone et al 2009;Goudfrooij et al 2011;Piatti et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Then the extent of the MSTO decreases again. Such a behavior is to be expected if stellar rotation causes the spread in the MSTO (Brandt & Huang 2015a;Niederhofer et al 2015b). However, there are two outliers to this relation, NGC 1795 at 1.4 Gyr and IC 2146 at 1.9 Gyr, which both have a compact MSTO structure.…”
Section: Correlations With Agementioning
confidence: 87%
“…Bastian & Silva-Villa (2013) and Niederhofer et al (2015a) found no evidence for age spreads comparable in duration to that suggested for the intermediate-age clusters in a sample of 14 young massive LMC clusters. There could be some spreads present in the young clusters (the case of NGC 1856 will be discussed in more detail below), however these spreads would be much smaller that those inferred for the intermediate-age clusters, and the spread is a function of cluster age (Niederhofer et al 2015b).…”
Section: Other Considerations On Age Spreads Within Clustersmentioning
confidence: 99%
See 1 more Smart Citation